Whole-body photobiomodulation therapy for chronic pain: a protocol for a feasibility trial - Nicola R Heneghan; Andrew Soundy; Bethany Fitzmaurice; Asius Rayen (BMJ Open, 2022)
Introduction Chronic pain conditions are a leading cause of disease and disability. They are associated with symptoms such as fatigue, sleep and mood disturbances. Minimal evidence is available to support effective treatments and alternatives treatment approaches are called for. Photobiomodulation therapy has been highlighted as one promising option. A whole-body therapy device (NovoTHOR) has recently been developed with a number of potential advantages for people with chronic pain. Research is needed to consider the feasibility of this device.Methods and analysis A single-centre single-armed (no placebo group) feasibility study with an embedded qualitative component will be conducted. The intervention will comprise 18 treatments over 6 weeks, with 6-month follow-up, in the whole-body photobiomodulation device. A non-probability sample of 20 adult participants with a clinician diagnosis of chronic axial pain, polyarthralgia, myofascial pain or widespread pain will be recruited (self-referral and clinician referral). Outcome measures will focus on acceptability of trial processes with a view to guiding a definitive randomised controlled trial. Analyses will use descriptive statistics for quantitative aspects. The qualitative element will be assessed by means of a participant-reported experience questionnaire postintervention and semistructured audio-recorded interviews at three stages; preintervention, midintervention and postintervention. The latter will be transcribed verbatim and a reflexive thematic analysis will be used to identify emerging themes. Exploratory outcomes (participant-reported and performance-based measures) will be analysed according to data distribution.Ethics and dissemination The study has received ethical approval from the Leicester Central Research and Ethics Committee. Findings will be disseminated via local chronic pain groups, public register update, submission for presentation at scientific meetings and open-access peer-reviewed journals, and via academic social networks.Trial registration number NCT05069363.